As you like it [Ako sa Vám páči anglicky] - Shakespeare, William, 1564-1616 (Sweet Cherry Publishing : [distributor] Sweet Cherry Publishing, 2020)
"All the world´s a stage..." One of the most quoted lines of Shakespeare was first heard in this play. "As you like it" is set in the enchanted Forest of Arden, where Rosalind, the daughter of an exil duke, and Orlando, the son of one of her father´s courters, become entangled in a game of love and mistaken identity.